The Pharmacokinetics of Doxycycline in Channel Catfish (Ictalurus punctatus) Following Intravenous and Oral Administrations - Xu, Ning; Fu, Yu; Cheng, Bo; Liu, Yongtao; Yang, Qiuhong; Dong, Jing; Yang, Yibin; Zhou, Shun; Song, Yi; Ai, Xiaohui (Frontiers in Veterinary Science, 2020)
The objective of this study was to investigate the bioavailability (BA) and pharmacokinetics (PK) of doxycycline (DC) in channel catfish (Ictalurus punctatus) following a single intravenous injection at 5 mg/kg and a single oral administration at 50 mg/kg at 24 ℃. The calculation of PK parameters was based on the software of 3P97. The plasma samples were determined using the ultra-performance liquid chromatography. Following oral administration, the multiple-peak phenomenon presented in concentration vs. time curve of DC at 2 h (107.01 mg/L), 8 h (55.07 mg/L), and 72 h (15.10 mg/L), respectively. The compartmental model can’t simulate the oral concentration vs. time profile beside a non-compartmental model. The calculated parameters of the elimination rate constant (λz), the elimination half-life (t1/2λz), and the area under concentration vs. time curve (AUC0-144) were 0.037 1/h, 18.91 h, and 2255.45 µg.h/mL, respectively. After intravenous administration, the concentration vs. time profile of DC was best described by a two-compartmental open model without absorption. The parameters of the distribution rate constant (α), the distribution half-life (t1/2), the elimination rate constant (β), the elimination half-life (t1/2β), the apparent distribution volume at steady state (Vss), the total clearance (Cl) and the area under concentration vs. time curve (AUC0-∞) were 2.79 1/h, 0.25 h, 0.042 1/h, 16.51 h, 300.00 mL/kg, 14.00 mL/h/kg, and 364.99 μg.h/mL, respectively. For the calculation of BA values at the same condition, the data obtained from intravenous injection were also iterated based on a non-compartmental model, and the corresponding parameters of λz, t1/2λz, Vz, Cl, and AUC0-144 were 0.019 1/h, 36.26 h, 480.00 mL/kg, 9.10 mL/h/kg, and 514.45 µg.h/mL, respectively. However, there was a considerable difference in the same parameter calculated by compartmental and non-compartmental approaches. Finally, a medium BA value of DC was evaluated to be 43.84%. This study will provide a framework for determining the BA of DC in the development of a new formulation in the future, and provide some information for the appropriate usage of DC in aquaculture.